Мультимедіа технології в сучасних інформаційних системах - Телятников, Г. А. (ХНУРЕ, 2025)
The development of multimedia technologies has significantly influenced various fields including education, entertainment, and business communications. Modern systems utilize advanced algorithms for audio and video processing, virtual and augmented reality, and artificial intelligence-driven multimedia content analysis. Compression techniques such as MPEG-4 and H.265, combined with machine learning-based enhancements, improve media quality and efficiency. The integration of interactive multimedia in web environments through HTML5 and WebGL enables the creation of dynamic and immersive applications. This study examines the latest advancements in multimedia technologies, highlighting their role in enhancing information systems and proposing strategies for optimizing their application.
Keywords: мультимедіа технології; multimedia technologie